Long-term outcomes of infantile spasms in children treated with ketogenic diet therapy in combination with anti-seizure medications in a resource-limited region - Liao, Jianxiang; Hu, Zhanqi; Lin, Sufang; Lu, Xinguo; Wen, Jialun; Duan, Jing; Zou, Dongfang; Zou, Huafang; Yu, Mei; Liu, Liqin; Qiao, Xiaoying; Ye, Yuanzhen (Frontiers in Epidemiology, 2023)
Objective: Despite numerous guidelines, the overall outcome of infantile spasms is poor, with only a small number of patients being able to attend school. The purpose of this study was to investigate the long term outcome.Patients had poor access to recommended first-line anti-seizure medications (ASMs), like hormones (corticotropin or prednisolone/prednisone) and vigabatrin, and their alternative treatment was other ASMs and ketogenic diet. Methods: Patients of infantile spasms with records over two years in the electronic medical record system during January 2014 and August 2022, were included in this study. The information of patients was retrospectively reviewed. All patients had received ketogenic diet therapy, mainly classical ketogenic diet therapy. The ketogenic diet therapy was combined with ASMs other than first line therapy. The primary end-point outcome measure was the number of patients with seizure freedom. The secondary measures included duration of ketogenic diet therapy, choice of ASMs, and patient development at the last visit. Results: A total of 177 patients with infantile spasms were included, and 152 (152/177, 86%) of them had seizure freedom. The median of duration from the first to the last hospital visit was 53.27 months, and the number of visits was 47.00. The median of age at initial hospital visit was 8.00 months, and the age at initiation of ketogenic diet was 17.73 months. At the last visit, the proportions of patients with neurodevelopmental delay, developmental epileptic encephalopathy, drug-resistant epilepsy and generalized seizures increased significantly. The frequently used ASMs were topiramate, valproic acid, levetiracetam, nitrazepam and vitamin B6 injection, while the recommended first-line drugs corticotropin and vigabatrin were rarely selected. The study duration of 9.5 years was divided into three periods, but the prescription of ASMs did not change significantly among these periods. Conclusions: Although the seizure freedom rate is high with ketogenic diet therapy combined with non-standard ASMs, the patients had significantly neurodevelopmental delay at the last visit, which is, however, similar with that of standard treatment. To improve the outcomes of infantile spasms, prospective and multicenter clinical trials of ketogenic diet as the first-line treatment in combination with non-standard ASMs are needed.